Interest Rates, Uncertainty and the Livingston Data - BOMBERGER, WILLIAM A.; FRAZER, WILLIAM J. (Journal of Finance, 1981)
ABSTRACT The observed relationship between the standard deviation of forecasts and past forecast errors as found in the Livingston survey suggests the interpretation of the standard deviation as a measure of inflation uncertainty. The mean and the standard deviation for the inflation rate forecast found in the Livingston survey, furthermore, are used as regressors in a reduced‐form interest rate equation. The results indicate a large negative effect of such uncertainty on interest rates. The inclusion of the uncertainty measure and commonly omitted lagged values of all variables in our analysis of data leads to more theoretically plausible estimated effects of money growth and expected inflation on interest rates than do standard estimates.